Modeling magneto-rheological damper using ANFIS method - Mohd Ridzwan, Hj Ramli (2012)
This thesis focused on the development Modeling Magneto-Rheological damper using Adaptive Neuro-Fuzzy Inference System (ANFIS) method. Magneto-Rheological (MR) damper is a semi-active control device and has been characterized by a set of nonlinear differential equations which represent a model of the MR damper. By using this mathematical model, the force of the MR damper is directly solved to a given displacement and applied current. However, solving the non-linear equations describing the performance of the MR damper may be difficult or time consuming to predict a required voltage. One of the methods to model the MR damper is using (ANFIS).It is faster than the mathematical model for keeping the error small. ANFIS has been effectively applied to model complex systems because of its great training process.